2019
DOI: 10.11114/ijsss.v7i5.4449
|View full text |Cite
|
Sign up to set email alerts
|

Improving Police Social Media Use Practices

Abstract: Phenomenological study findings identified police social media site use practices that law enforcement leadership may wish to consider incorporating. Findings showed that members of the public in their lived experiences desired two-way asynchronous and synchronous interpersonal communication capabilities when accessing social media platforms maintained by law enforcement agencies. Improved police social media use practices in these areas may be a gateway to building stronger community relations and using socia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“…Research to date exploring police social media usage tends to demonstrate that communication has not been a two-way process (Brainard and McNutt, 2010;Crump, 2011;Lieberman et al, 2013;Grimmelikhuijsen & Meijer, 2015;Beshears, Beshears & Bond, 2019 were the most used (49.4%), followed by posts in relation to: public relations (31%), information about officer injuries (3.7%), alerts (3.5%), crime prevention and community safety tips (3.0%), driving under the influence (1.7%), missing persons (1.6%), direction to services (1.3%), other posts (4.1%), and posts that could not be categorised (0.7%). A further interesting facet to Liberman and colleagues 2013 Understanding the police's use of social media has been a topic of academic exploration but has primarily been limited to describing the actions of the police on social media as opposed to evaluating the effectiveness of such actions (Hu, Rodgers & Lovrich, 2018).…”
Section: Cust_social_implications_(limit_100_words) :No Data Availablementioning
confidence: 99%
See 4 more Smart Citations
“…Research to date exploring police social media usage tends to demonstrate that communication has not been a two-way process (Brainard and McNutt, 2010;Crump, 2011;Lieberman et al, 2013;Grimmelikhuijsen & Meijer, 2015;Beshears, Beshears & Bond, 2019 were the most used (49.4%), followed by posts in relation to: public relations (31%), information about officer injuries (3.7%), alerts (3.5%), crime prevention and community safety tips (3.0%), driving under the influence (1.7%), missing persons (1.6%), direction to services (1.3%), other posts (4.1%), and posts that could not be categorised (0.7%). A further interesting facet to Liberman and colleagues 2013 Understanding the police's use of social media has been a topic of academic exploration but has primarily been limited to describing the actions of the police on social media as opposed to evaluating the effectiveness of such actions (Hu, Rodgers & Lovrich, 2018).…”
Section: Cust_social_implications_(limit_100_words) :No Data Availablementioning
confidence: 99%
“…However, the extent to which the police use social media under the principles of a community policing strategy has been questioned. Research to date exploring police social media usage tends to demonstrate that communication has not been a two-way process (Brainard and McNutt, 2010; Crump, 2011; Lieberman et al , 2013; Grimmelikhuijsen and Meijer, 2015; Beshears et al , 2019). For example, Crump (2011) reviewed the actions of UK police on Twitter and suggested that the police’s use of Twitter was most successfully used as a one-way communication strategy only and there was very little evidence of open communication between citizens and the police.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations